Establishing Competency Standards of Implementing Green Citizen Skills To Strengthen Employability of Green Jobs - Surono, Surono (Pelopor Publikasi Akademika, 2025)
This study addresses the global shift towards sustainable economies, which requires a workforce with proficiency in green practices. The research develops competency standards for Green Citizen Skills, aimed at enhancing employability in green jobs and responding to the increasing demand for sustainability-focused skills. A mixed-methods approach, including literature reviews, expert consultations, and validation through Delphi methods, was employed to formulate actionable frameworks for integrating Green Citizen Skills into vocational education and training systems. The findings highlight the alignment of key elements such as Unit of Competency, Unit Titles, and Performance Criteria with vocational frameworks, ensuring their relevance and adaptability across both educational and professional contexts. Furthermore, competency components like Range of Variables and Critical Aspects are connected to sustainability principles, resource efficiency, and active community engagement, promoting a holistic approach to green job readiness. This study emphasizes the importance of bridging the skills gap between educational outputs and industry demands, fostering a workforce capable of contributing to sustainable development goals. The developed standards provide practical tools to enhance green job preparedness, empowering individuals to support economic, social, and environmental sustainability. Ultimately, this research contributes to the creation of a skilled workforce equipped to drive the transition to a more sustainable global economy.